Empowering Leadership in Creativity and Work-Effort: An Elucidation through the Psychological Empowerment and Self- Leadership of the Millennials Generation - Muhammad Ikhsan Alif; Tur Nastiti (Gadjah Mada International Journal of Business, 2022)
The purpose of this article is to elucidate the relations of empowering leadership on creativity and work-effort by using psychological empowerment and self-leadership. This elucidation contributes to fill the void in empirical studies by simultaneously examining the dynamics of relations among empowering leadership, creativity, work-effort, psychological empowerment, and self-leadership. The social exchange theory is applied to theoretically explain the psychological mechanisms among the constructs. As millennials are categorized as a creative generation, this study focuses on discussing the factors influencing their creativity and work-effort, with a specific notion of empowerment. This study is based on survey data (n = 113) of millennial generation employees working in digital start-up creative industries in Indonesia. Partial least squares structural equation modeling (PLS-SEM) is used to estimate the model. Results of the study find that empowering leadership influences employee creativity and work-effort either directly or indirectly through psychological empowerment and self-leadership. More specifically, the psychological empowerment of employees partially mediates the influence of empowering leadership on employee creativity and employee work-effort. Employee self-leadership also partially mediates the effect of empowering leadership on psychological empowerment, creativity, and employee work-effort. This study implies the practical and theoretical application of empowering leadership in the creativity context of the millennial generation.